Heartbreak for Sabah - Xavier, Francis (New Sabah Times English (KK), 2016)
KOTA KINABALU: Sabah women were left 'brokenhearted' for the second year running after losing 2-3 to MISC-MIFA in the final of the 29th Tun Sharifah Rodziah Football Tournament in Sintok, Kedah yesterday.